Impact of Internal Migration and Other Significant Factors on Improving Labor Productivity of Agricultural Sector - Silva, G.R.P. (My University, 2012)
Escalated amount of studies are being carried out by various scholars from different disciplines to estimate the extent to which labor productivity and its impact on various economic and social aspects. Primarily this study focuses on examining the relationship between labor productivity and internal migration in Sri Lanka for last 10 years. Based on the significance of the factors on labor productivity, production function was developed for the agricultural sector. Factors that are making impact on the migration are recognized based on the internal migration function. Indirect elasticity was used to analyze the bond between agricultural sector labor productivity on internal labor migration. Data were collected from secondary sources pertaining to labor productivity and internal migration during last thirty years and primary data were collected through focus group discussions. Research finding indicates that the literacy, usage of fertilizer and pesticide and production methods have significant impact on the agricultural sector productivity. Additionally wage dissimilarity and age structure has momentous impact on internal migration from rural to urban. Further it is clearly indicated that the equal distribution of power and resources and reduction in economic discrepancy among provinces could be used as tools in controlling the internal labor migration. However fair distributions of the value addition made by the agricultural sector among contributors assume to be much poor and it is considered as one of the major requirement expected by the agricultural sector participants. Improvements in the nature and the quality of the product would be substantially important for the successful addressing the internal migration issue.